A study to evaluate the effects of nutritional intervention measures on children admitted in the nutritional rehabilitation center (Bal Sanjeevani Kendra) of Surendranagar district - Bhimani, Nishant R.; Vachhani, Pushti V.; Kartha, Girija P. (International Journal of Research in Medical Sciences, 2017)
Background:The life cycle dynamics of the causes and consequences of malnutrition demand a holistic and all inclusive approach to prevent and treat under-nutrition and nutritional deficiencies. In response, Government of Gujarat launched “Mission Balam Sukham” in the year 2012 which focuses on both preventive and curative aspects. Curative aspect consist of three tier approach for integrated management of malnutrition at three different levels. Nutritional rehabilitation Center is a unit in a district health facility where children with severe acute malnutrition are admitted and provided with the nutritional & therapeutic care. Methods: Analysis of data of all the children admitted to Nutritional Rehabilitation Centre of Surendranagar district from June-2012 to November 2013. Statistical analysis was done using SPSS. Results: A total of 280 children were included in the study. The overall mean weight at admission was found 8.30 kg with standard deviation of 2.09 kg and the mean weight at the time of discharge was 8.97 kg with standard deviation of 2.16 kg. Average weight gain among 141 boys was 6.63 g/kg/day and among girls was found 7.60 g/kg/day. Out of total 280 children, 103 (36.79%) children had weight gain as per the standard criteria (8 gm/kg/day). Diarrhoea was found to be the associated medical condition in majority of the children. Out of total 184 children without medical complications, 97 (52.72%) children had weight gain as per the standard criteria. Conclusions: Present study reflected that Nutritional Rehabilitation Centers have been playing a key role to cope with malnutrition as demonstrated by high weight gain rate as well as high recovery rate.